Aprendizado a partir do erro: uma análise no nível individual no local de trabalho - Sbrissa, Elaine Cristina da Costa Carreira (2020)
Learning from an error is crucial for the development of individuals and organizations. Errors cannot be eliminated in their entirety, even if there are strategies to avoid or prevent them (FRESE; KEITH, 2015). Numerous factors may contribute to cover-up an error or learning from a misunderstanding; and an open and positive organizational posture towards these errors would directly impact the orientation for learning, innovation, and change (RYBOWIAK et al., 1999). Despite it, this learning is not an automatic process and various aspects might influence it (GROHNERT; MEUWISSEN; GIJSELAERS, 2019). The essay aims to propose and test a learning model based on errors and their antecedents to relate the inclusive leadership, psychological security, support context, and self-efficacy in the individual's perspective within the organizational environment. The quantitative approach was adopted by using a sample of 242 individuals working in organizations and having leaders or supervisors. The data analysis was performed by modeling structural equations. The results indicated positive relationships between inclusive leadership and self-efficacy with learning from error. The relationship in advance of the support context with psychological security was confirmed as well. The relationship between psychological security and learning from error was not confirmed, although. Therefore, the moderating effect of self-efficacy was not confirmed. As practical implications, this dissertation contributes to a clearer organizational vision, directing the development of actions and a better understanding of the conditions and circumstances that facilitate or hinder learning from error. According to the results, invest in the development of individuals' capacities and skills provides additional results than invest in the organizational environment. It must be considered that the leadership style with openness, accessibility, and availability is also a remarkable aspect. Talent acquisition processes may have strategies that consider the reality presented here. The study contributed to the development of specific theoretical and empirical knowledge about the factors that influence learning from error. It is not released of limitations, indeed. The use of a diversified sample is a limitation due to not being possible to guarantee that all biases were eliminated, even though including a variable control that minimizes possible biases caused by foreign variables (confounders). The data collected considered the team members and not the leaders' view. It is a factor that can contribute to understanding. In addition to the issues mentioned above, future research may explore a background related directly to individuals and not just the context, and inquiries may be carried out in a single large company with mixed methods to explore the influence of contextual variables.